2018
DOI: 10.1155/2018/3505428
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis of Rhodococcus Sp. DSSKP-R-001: A Highly Effective β-Estradiol-Degrading Bacterium

Abstract: We screened bacteria that use E2 as its sole source of carbon and energy for growth and identified them as Rhodococcus, and we named them DSSKP-R-001. For a better understanding of the metabolic potential of the strain, whole genome sequencing of Rhodococcus DSSKP-R-001 and annotation of the functional genes were performed. The genomic sketches included a predicted protein-coding gene of approximately 5.4 Mbp with G + C content of 68.72% and 5180. The genome of Rhodococcus strain DSSKP-R-001 consists of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…: WPAG00000000.1), which is also present in the genome of oestrogen-degrading Rhodococcus sp. strain DSSKP-R-001 (Zhao et al, 2018), but not in other Rhodococcus members incapable of degrading oestrogen. Moreover, the two homologous oestrogen-degrading gene clusters are both located on their megaplasmids (Fig.…”
Section: Identification Of the Oestrogen-degrading Genes Via Comparatmentioning
confidence: 90%
“…: WPAG00000000.1), which is also present in the genome of oestrogen-degrading Rhodococcus sp. strain DSSKP-R-001 (Zhao et al, 2018), but not in other Rhodococcus members incapable of degrading oestrogen. Moreover, the two homologous oestrogen-degrading gene clusters are both located on their megaplasmids (Fig.…”
Section: Identification Of the Oestrogen-degrading Genes Via Comparatmentioning
confidence: 90%
“…For example, Rhodococcus equi Y50156 and Rhodococcus zopfii Y50158 have a degradation rate > 95 % at 24 h for 100 mg/L concentrations of the four estrogens listed above [11], and Rhodococcus rubber KC4 has a 99% degradation rate at 24 h for E2a at a concentration of 3 mg/L [15]. In our previous study, the degradation rate at 72 h for 50 mg/L E2 by R. equi DSSKP-R-001 was 97% [35], and the degradation rates at 96 h of 30 mg/L E1, E2, and EE2 were 100%, 100%, and 90%, respectively. Therefore, the Rhodococcus.…”
Section: Introductionmentioning
confidence: 88%
“…Zhao and co-workers state that Rhodococcus strain sp. DSSKP-R-001, interesting for its beta-estradiol-degrading potential, contains 8 CRISPRs [144]. However, the authors do not state how these were identified.…”
Section: Discussionmentioning
confidence: 99%